Role of thoracic consolidation radiation in extensive stage small cell lung cancer: A systematic review and meta-analysis of randomised controlled trials - Rathod, Shrinivas; Jeremic, Branislav; Dubey, Arbind; Giuliani, Meredith; Bashir, Bashir; Chowdhury, Amitava; Liang, You; Pereira, Sandra; Agarwal, JaiPrakash; Koul, Rashmi (European journal of cancer (1990), 2019)
Extensive stage small cell lung cancer (ES-SCLC) carries a poor prognosis, and the thoracic progression is common. Consolidation radiation to thoracic disease (cRT) could improve progression-free survival (PFS) and overall survival (OS). We conducted an electronic search of PubMed and Embase with no language, year or publication status restrictions and evaluated randomised controlled trials (RCTs) addressing the role of cRT in ES-SCLC. Preferred Reporting of Systematic Reviews and Meta-Analyses guidelines for systematic review and Cochrane methodology for meta-analysis were followed. Effect estimates (hazard ratios [HRs] and confidence intervals [CIs]) and risk ratios were extracted, with a fixed/random-effects model created to estimate treatment effects. I2 statistics and heterogeneity statistics were performed. Comprehensive and systematic search identified 1107 records, after removal of duplicate records screened 922 records, assessed 31 full-text articles for eligibility and 3 RCTs with a total of 690 patients were included. Pooled analysis showed cRT significant improved PFS (p < 0.0001) with HR 0.72 (95% CI: 0.61–0.83, I2-0%). In addition, cRT significantly (p < 0.001) reduced the risk of thoracic progression as the first site of progression with a relative risk of 0.52 (95% CI: 0.44–0.61, I2-0%). OS analysis showed no significant (p = 0.36) benefit with HR of 0.88 (95% CI 0.66–1.18, I2-52%) with cRT. Pooled meta-analysis of 3 randomised controlled studies shows consolidation thoracic radiotherapy (RT) offers significant improvement in PFS and reduction in thoracic failures. Further research on subclassification of ES-SCLC (limited vs extensive metastasis), optimise strategy for RT integration (sequential vs concurrent) and optimal RT dose is needed to identify the subset of ES-SCLC likely to have significant OS benefit. •Systematic review and meta-analysis of RCT evaluating consolidation radiation to thoracic disease (cRT) in extensive stage small cell lung cancer (ES-SCLC).•cRT significantly improves progression-free survival in ES-SCLC.•cRT significantly improves reduces thoracic failures in ES-SCLC.